Implementation of Baznas RI Decree Number 1 of 2024 Concerning the Nisab of Income Zakat and Its Impact on Civil Servant Compliance - jamal; Hidayat; Hendra Kholid (LP2M IAIN Palopo, 2025)
The Decree of the Chairman of BAZNAS RI Number 1 of 2024 provides clear guidance on the provisions and procedures for calculating zakat on income and services, with the hope of increasing awareness and compliance among State Civil Apparatus (ASN). This study focuses on analyzing the implementation of this decree at BAZNAS RI and evaluating its impact on the compliance of State Civil Apparatus (ASN) in paying zakat on income and services. In conducting this research, the author used a field research method with a qualitative research type in the form of a case study with an empirical juridical (socio-legal) approach. The results of the study show that: First, the Decree of the Chairman of BAZNAS RI No. 1 of 2024 stipulates zakat on income with a nisab of 85 grams of gold and a level of 2.5% of gross income. This decree uses the qiyas syabah approach which combines the principles of gold zakat (nisab and level) with agricultural zakat (payment time). Second, the Implementation of the Decree of the Chairman of BAZNAS RI No. 1 of 2024 was carried out with three approaches, namely: (1) Implementation of the Integrated Marketing Communication (IMC) strategy by combining the Above The Line (ATL) and Below The Line (BTL) approaches, (2) segmentation of prospective muzakki, (3) establishing cooperation with the National Zakat Collection Institution (LAZNAS). Third, the Implementation of the Decree of the Chairman of BAZNAS No. 1 of 2024 has had a significant impact on the collection of income and service zakat. This is indicated by a 20.62% increase in BAZNAS's zakat maal collection in the first semester of 2024.